Menstruation Matters : Challenging the Law's Silence on Periods - Crawford, Bridget J.; Waldman, Emily Gold (Book collections on Project MUSE., 2022)
"In this book, the authors explore the many ways that menstruation makes a difference in law and life in the United States. The book looks at cultural attitudes toward menstruation, the tampon tax, the need for accessible products in schools, prisons, and other public buildings, employment discrimination matters, health and environmental concerns, the complex market for menstrual products, and the ways similar issues at the intersection of menstruation and law arise in other countries. This book asks what the law currently says about menstruation (spoiler alert: not much, at least not explicitly) and lays out concrete suggestions for legal reform. The authors aim to transform the law and society so that every person can participate fully in all aspects of public and private life, without regard to the involuntary biological process of menstruation"-- Provided by publisher